2021
DOI: 10.1172/jci.insight.143650
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone does not synergize with mirabegron to increase beige fat or further improve glucose metabolism

Abstract: BACKGROUND. Beige and brown adipose tissue (BAT) are associated with improved metabolic homeostasis. We recently reported that the β3AR agonist mirabegron induced beige adipose tissue in obese insulin resistant subjects, and this was accompanied by improved glucose metabolism. Here we evaluated pioglitazone treatment with a combination pioglitazone and mirabegron treatment, and compared these to previously published data evaluating mirabegron treatment alone. Both drugs were used at FDA-approved dosages. METHO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 68 publications
(169 reference statements)
0
19
0
Order By: Relevance
“…Another open-label study showed that 12-week mirabegron treatment (50 mg/day) of healthy individuals led to increased WAT expression of UCP1, TMEM26, CIDEA proteins, and phosphorylation of hormone-sensitive lipase on serine 660, suggesting considerable browning of subcutaneous WAT with prolonged treatment with mirabegron ( 681 ). Another study by the same group extended these findings by showing that pioglitazone 30 mg/day for 12 weeks in overweight or obese participants also resulted in WAT browning, but that combined treatment with mirabegron + pioglitazone actually reduced WAT browning marker levels compared to monotherapy ( 682 ). None of the treatment arms led to increased cold-induced BAT 18 FDG uptake.…”
Section: Pharmacological Activation Of Brown Adipose Tissuementioning
confidence: 93%
See 1 more Smart Citation
“…Another open-label study showed that 12-week mirabegron treatment (50 mg/day) of healthy individuals led to increased WAT expression of UCP1, TMEM26, CIDEA proteins, and phosphorylation of hormone-sensitive lipase on serine 660, suggesting considerable browning of subcutaneous WAT with prolonged treatment with mirabegron ( 681 ). Another study by the same group extended these findings by showing that pioglitazone 30 mg/day for 12 weeks in overweight or obese participants also resulted in WAT browning, but that combined treatment with mirabegron + pioglitazone actually reduced WAT browning marker levels compared to monotherapy ( 682 ). None of the treatment arms led to increased cold-induced BAT 18 FDG uptake.…”
Section: Pharmacological Activation Of Brown Adipose Tissuementioning
confidence: 93%
“…However, pioglitazone treatment for 28 days in humans did not induce WAT browning and even led to reduced cold-induced BAT glucose uptake in 1 study ( 635 ). Another study found a significant increase in subcutaneous WAT browning markers after 12 weeks of treatment with pioglitazone 30 mg per day in overweight or obese individuals, but again without an increase in cold-induced BAT glucose uptake ( 682 ). The clinical significance of WAT browning for the marked antidiabetic effects of PPAR-γ agonists is unclear at the moment, whereas the metabolic activation of BAT through PPAR-γ agonists is unlikely in humans.…”
Section: Pharmacological Activation Of Brown Adipose Tissuementioning
confidence: 99%
“…The role of macrophages in adipose tissue under different physiological settings such as obesity has been widely studied 25 , 26 . Macrophages are key mediators of low grade adipose tissue inflammation in obesity, promoting insulin resistance 26 .…”
Section: Discussionmentioning
confidence: 99%
“…One study used Computer Tomography to examine muscle mass and body composition, and four used Dual Energy X-ray Absorptiometry (DEXA). In 44 patients, appendicular lean mass measured by CT was unaffected by low dose pioglitazone (15mg 3 weeks followed by 30mg for 3 weeks) 23 , and a 30mg/12 week regimen had no effect in 12 patients 25 . In 2 studies of 23 patients randomised to pioglitazone 45mg/10-16 weeks, an increase in lean body mass of 1.8-1.92kg was seen using Dual-energy X-ray absorbtiometry 26,27 .…”
Section: Body Compositionmentioning
confidence: 96%